Analysis of codon usage patterns in complete plastomes of four medicinal Polygonatum species (Asparagaceae) - Shi, Naixing; Yuan, Yiwen; Huang, Renjie; Wen, Guosong (Frontiers in Genetics, 2024)
Polygonati Rhizoma and Polygonati odorati Rhizoma, known as “Huangjing” and “Yuzhu” in China, are medicinal Polygonatum species resources with top-grade medical and edible properties. The chloroplast (cp) genome has been used to study species diversity, evolution, and breeding of species for applications in genetic engineering. Codon usage bias (CUB), a common and complex natural phenomenon, is essential for studies of codon optimization of exogenous genes, genetic engineering, and molecular evolution. However, the CUB of medicinal Polygonatum species chloroplast genomes has not been systematically studied. In our study, a detailed analysis of CUB was performed in the medicinal Polygonatum species chloroplast genomes. We investigated the codon bias of 204 plastid protein-coding genes (PCGs) in 4 medicinal Polygonatum species using CodonW and CUSP online software. Through the analysis of the codon bias index, we found that the medicinal Polygonatum species chloroplast genomes had weak codon usage bias. In addition, our results also showed a high preference for AT bases in medicinal Polygonatum species chloroplast genomes, and the preference to use AT-ending codons was observed in these species chloroplast genomes. The neutrality plot, ENC plot, PR2-Bias plot, and correspondence analysis showed that compared with mutation pressure, natural selection was the most important factor of CUB. Based on the comparative analysis of high-frequency codons and high expression codons, we also determined the 10-11 optimal codons of investigative medicinal Polygonatum species. Furthermore, the result of RSCU-based cluster analysis showed that the genetic relationship between different medicinal Polygonatum species could be well reflected. This study provided an essential understanding of CUB and evolution in the medicinal Polygonatum species chloroplast genomes.